(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
The article examines the genre of elegy in a diachronic, historical and literary aspect. The modification of the genre is traced throughout various pathological epochs. Genre features of elegy at various stages of the genre functioning are investigated. The question of the correlation of the concepts of "elegiac genre" and "elegiac mode" is considered. The hypothesis of "elegization" of literature is put forward by analogy with the principle of "romanization" of literature by M. M. Bakhtin.